ECTRIMS/EAN guideline on the pharmacological treatment of people with multiple sclerosis - Montalban, X; Gold, R; Thompson, A J; Otero-Romero, S; Amato, M P; Chandraratna, D; Clanet, M; Comi, G; Derfuss, T; Fazekas, F; Hartung, H P; Havrdova, E; et al. (European journal of neurology, 2018)
BACKGROUND AND PURPOSE: Multiple sclerosis (MS) is a complex disease of the central nervous system. As new drugs are becoming available, knowledge on diagnosis and treatment must continuously evolve. There is therefore a need for a reference tool compiling current data on benefit and safety, to aid professionals in treatment decisions and use of resources across Europe. The European Committee of Treatment and Research in Multiple Sclerosis (ECTRIMS) and the European Academy of Neurology (EAN) have joined forces to meet this need. The objective was to develop an evidence-based clinical practice guideline for the pharmacological treatment of people with MS to guide healthcare professionals in the decision-making process. METHODS: This guideline has been developed using the GRADE methodology and following the recently updated EAN recommendations for guideline development. Clinical questions were formulated in PICO format (patient, intervention, comparator, outcome) and outcomes were prioritized according to their relevance to clinical practice. An exhaustive literature search up to December 2016 was performed for each question and the evidence is presented narratively and, when possible, combined in a meta-analysis using a random-effects model. The quality of evidence for each outcome was rated into four categories - very high, high, low and very low - according to the risk of bias. GRADE evidence profiles were created using GRADEprofiler (GRADEpro) software (Version 3.6). The recommendations with assigned strength (strong, weak) were formulated based on the quality of evidence and the risk-benefit balance. Consensus between the panellists was reached by use of the modified nominal group technique. RESULTS: A total of 10 questions have been agreed, encompassing treatment efficacy, response criteria, strategies to address suboptimal response and safety concerns and treatment strategies in MS and pregnancy. The guideline takes into account all disease-modifying drugs approved by the European Medicine Agency at the time of publication. A total of 20 recommendations were agreed by the guideline working group members after three rounds of consensus.
Keywords: směrnice pro lékařskou praxi jako téma; diseases; Societies, Medical; GRADE methodology; Practice Guidelines as Topic; roztroušená skleróza; Europe; Evropa; společnosti lékařské; neurologie; research methods; Neurology; Multiple Sclerosis; Humans; guideline; neurological disorders; demyelinating; disease-modifying treatment; lidé; multiple sclerosis